An Exploratory Structural Equation Model of Stress-Related Experiences Among Justice-Involved Youth: A Gender Comparison. (February 2020) - Dembo, Richard; Krupa, Julie M.; Wareham, Jennifer; Faber, Jessica; Cristiano, Jennifer; Diclemente, Ralph J.; Terminello, Asha; Schmeidler, James
Youth involved in the juvenile justice system demonstrate greater risk of exposure to negative life experiences. The present study explores the prevalence of three stress-related experiences (sexual assault victimization, bullying/victimization, and minority sexual orientation) among newly arrested adolescents. Gender (biological sex) differences were examined as well as associations with sociodemographic characteristics, depressive symptoms, substance use, and sexually transmitted infection (STI). Factor analyses found a single factor of stress for both genders. Prevalence rates for bullying/victimization, sexual assault victimization, and sexual minority status were higher for girls than boys. Girls were also more likely than boys to test positive for STIs and experience depressive symptoms, while boys were more likely than girls to test positive for marijuana use. Depression and drug-related problems were associated with the stress construct for girls only. Bivariate comparisons with the three stress measures and sociodemographic characteristics indicated age and race effects. Implications are discussed.